2013
DOI: 10.1021/ie302604m
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally Stable Bimodal Aluminosilicates with Enhanced Acidity by Combination of Zeolite Y Precursors Assembly and the pH-Adjusting Method

Abstract: Through a combination of Y zeolite precursors and the pH-adjusting method, bimodal aluminosilicates (denoted as LFs) with strong acidity and excellent hydrothermal stability were synthesized. The hydrothermal stability of the resulting aluminosilicates was improved greatly by taking advantage of Y zeolite precursors (the retaining ratio of the total surface area was 33% after hydrothermal treatment in 100% water vapor at 800 °C for 15 h). When the mesostructure was basically formed in the first crystallization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 48 publications
4
39
0
Order By: Relevance
“…On the other hand, it should be noted that at the same initial Si/Al ratio of 30, the acid site density of SAZ-30 is higher than that of Al-SBA-15. This result further supports the work of Han et al [ 6 ] and others [ 7 , 8 , 9 , 18 ] who found that the introduction of zeolite building units in the mesopore walls induced an improved acidity of SBA-15 analogs.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, it should be noted that at the same initial Si/Al ratio of 30, the acid site density of SAZ-30 is higher than that of Al-SBA-15. This result further supports the work of Han et al [ 6 ] and others [ 7 , 8 , 9 , 18 ] who found that the introduction of zeolite building units in the mesopore walls induced an improved acidity of SBA-15 analogs.…”
Section: Resultssupporting
confidence: 91%
“…[46][47][48] Solid state NMR spectroscopy (Table 2) was employed for indepth characterization of the aluminosilicate xerogel matrix. 13 C CPMAS NMR spectrum of non-templated sample (SiAl1) displayed resonances of residual organic groups (Fig. 5S †).…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] For example, the authors of the present investigation have prepared hydrothermally stable mesophase by assembling Beta and Y precursors with P123. [9][10][11][12][13] Unfortunately, macropores are still absent in these materials, and so forth, which limit their practical application. Therefore, one effective solution to this problem is to develop a novel preparation strategy for the immobilization of macropores into the meso-microporous materials.…”
mentioning
confidence: 99%
“…Moreover, the authors of the present investigation have prepared mesoporous aluminosilicates (denoted as LFs) by combination of precursors assembly and pH-adjusting method and the yield of light fraction oil of LF-3 is 67.19%. 9 It is generally accepted that the activity of catalysts also depends on the acidity. In Cat-2, 5% MSA replaces 5% kaolin in Cat-1.…”
mentioning
confidence: 99%